Evaluation of nutrition literacy and nutrition knowledge level in nursing students: a study from Turkey - Özge Mengi Çelik; Remziye Semerci (BMC, 2022)
Abstract Objective The determination of nutritional knowledge and nutrition literacy among nursing students will enable nursing departments to establish the needs and solutions to enhance nutrition education in their education programs. Therefore, this study is aimed to evaluate the nutrition literacy and nutrition knowledge level of nursing students. Method The study data were collected with 'Information Form', 'Anthropometric Measurements', 'Nutrition Knowledge Level Scale for Adults', and 'Evaluation Instrument of Nutrition Literacy on Adults'. Analyzes were performed using descriptive and nonparametric tests. Results The score of nutrition knowledge is 56.6 ± 6.8 and 50.5% of them have a good nutrition knowledge level. The total nutrition literacy score is 28.6 ± 4.4 and 91.6% of them have a sufficient nutrition literacy level. It was no significant difference between students' characteristic features and nutrition knowledge score and nutrition literacy total score (p > 0.05). There was a statistically significant positive correlation between the nutrition knowledge score and the nutrition literacy total score and the nutrition literacy sub-sections scores (p < 0.05). Conclusion It has been determined that the nutrition knowledge and nutrition literacy levels of nursing students correlated with each other. To improve students' nutrition knowledge levels, as well as to improve their nutrition literacy and prevent non-communicable diseases nutrition lessons should be included in the curriculum.